Panorama das teorias de alfabetizaçao na América Latina nas últimas décadas (1980-2010) - Castedo, Mirta (2011)
Over the last 30 years fundamental changes have taken place in theories of literacy. In Latin America, they have affected teaching in different ways. Meanwhile other changes were occurring in literacy. From the survey of literature distributed in Latin America, in this article are studied three theories on the acquisition of written language with important implications for the field of literacy: the Whole Language, the phonological awareness and the psychogenetic theory. These theories are those that have been more reported in the region. The relationship oral-written language, the concept of error and linguistic diversity and variation are the axes that pass through the major points of agreement and disagreement between theories